Costs of injury in New Zealand: Accident Compensation Corporation spending, personal spending and quality-adjusted life years lost. Issue 2 (15th June 2012) - Wilson, Ross; Derrett, Sarah; Hansen, Paul; Langley, John Desmond
Abstract : Background: New Zealand offers a unique opportunity for cost-of-injury research due to its comprehensive, no-fault injury compensation insurance scheme, which is managed by the government-controlled Accident Compensation Corporation (ACC). Objectives: To estimate the costs of injury in New Zealand with respect to ACC's spending for entitlement claimants (ie, people with injuries requiring more than 'treatment only'), as well as injured individuals' out-of-pocket personal spending and non-pecuniary costs in terms of effects on health-related quality of life (HRQoL). Methods: A prospective cohort study of people injured between June 2007 and May 2009 was followed for 12 months after injury. ACC's spending for each participant (n=2215) was estimated from ACC data. Out-of-pocket personal spending and quality-adjusted life years (QALYs) lost were estimated based on interviews conducted at 3, 5 and 12 months post injury. Results: For the cohort studied, most of the reported financial costs of injury were met by ACC. ACC spending was higher for individuals with more severe injuries and ones admitted to hospital. There was no difference in mean personal spending between people who were hospitalised or not, or between those with minor or moderate injuries, although individuals with more severe injuries reported higher personal spending. Conclusions: Overall, the ACC appears to be performing well supporting injured people financially. Nonetheless, people with more severe injuries incur substantial out-of-pocket expenses. Costs are higher for hospitalised and more severe injuries, but non-hospitalised and less severe cases can still incur substantial costs. The HRQoL effects of injury—naturally, borne by injured individuals themselves—are relatively large on average.